2010
DOI: 10.1149/1.3290778
|View full text |Cite
|
Sign up to set email alerts
|

Tin Nitride Thin Films as Negative Electrode Material for Lithium-Ion Solid-State Batteries

Abstract: Tin nitride thin films have been reported as promising negative electrode materials for lithium-ion solid-state microbatteries. However, the reaction mechanism of this material has not been thoroughly investigated in the literature. To that purpose, a detailed electrochemical investigation of radio-frequency-sputtered tin nitride electrodes of two compositions (1:1 and 3:4) is presented for several layer thicknesses. The as-prepared thin films have been characterized by Rutherford backscattering spectrometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 51 publications
(89 reference statements)
5
35
0
Order By: Relevance
“…This effect was attributed to the formation of the Li 2 O framework that stabilizes the shrinking and expanding metal particles. [ 158 ] Also several nitrides were reported to undergo a similar alloying storage reaction, such as SnN x , [ 159 ] Zn 3 N 2 [ 160 ] and Ge 3 N 4 . [ 161 ] …”
Section: Conversion Anodesmentioning
confidence: 99%
“…This effect was attributed to the formation of the Li 2 O framework that stabilizes the shrinking and expanding metal particles. [ 158 ] Also several nitrides were reported to undergo a similar alloying storage reaction, such as SnN x , [ 159 ] Zn 3 N 2 [ 160 ] and Ge 3 N 4 . [ 161 ] …”
Section: Conversion Anodesmentioning
confidence: 99%
“…The electrochemical performance of Sn 3 N 4 electrodes in lithium cells has only previously been investigated using samples in thin lm form. 28,29 Hence, the Sn 3 N 4 /acetylene black/ sodium alginate electrodes described above were also examined in lithium half cells with a standard LiPF 6 /EC/DMC electrolyte. As in the sodium cells reduction and alloying could be envisaged as shown in the following equations, based on which the theoretical capacity is 1560 mA h g À1 and charge/discharge at 100 mA g À1 is equivalent to a C-rate of C/15.6.…”
Section: Electrochemical Behaviour Of Sn 3 N 4 In Lithium Half Cellsmentioning
confidence: 99%
“…Baggetto et al observed similar capacity losses from thin lm electrodes, but were able to extend the lifetime of the electrodes by limiting the potential range over which they cycled. 29 In order to understand the charge storage mechanism of Sn 3 N 4 in Li half-cells, ex situ XRD data were collected (Fig. 7).…”
Section: Electrochemical Behaviour Of Sn 3 N 4 In Lithium Half Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…3Co 0 + 4 Li 2 O. Lithium storage by means of conversion reactions has also been observed in other transition metal compounds, such as sulfides [8] and nitrides. [9] Although the cycling performances of these compounds are not satisfactory at present, such reaction provides highly active transition metal atoms that might interact with PPy and form PPymetal complexes.…”
Section: Introductionmentioning
confidence: 99%